Pudarnya Penggunaan Bahasa Indonesian Di Kalangan Remaja Akibat Pengaruh Bahasa Gaul - Devi Hertina Panjaitan; Rina Devianty (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The use of language is essential to human survival in all aspects of daily life. Language allows us to share our thoughts, feelings, desires, opinions, and information, among other things. Adolescents' proficiency in using proper Indonesian has started to decrease. One of the reasons Indonesian proficiency is declining among adolescents is the influence of slang. When people use Indonesian in formal settings, slang can get in the way, leading to bad grammar and spelling. Using both primary and secondary sources, this study embraces qualitative research methods and journal articles. Methods such as recording, observation, and interviews were employed to gather data. All things considered, these results point to environmental, developmental, and technological factors as the primary causes of the widespread use of slang among adolescents.